NLFE investigation on the FRP bar reinforced concrete deep beams with and without openings. (29th March 2019) - Ramadass, S.; Thomas, Job
This study reports the details of the nonlinear finite element (NLFE) analysis to predict the load-deflection response of twelve concrete deep beams reinforced with fibre reinforced polymer (FRP) bars that failed in shear. The analysis is carried out using the ANSYS software and the validation of the analysis is made by predicting the behaviour of the beams tested in the laboratory. The influence of the location of openings in the deep beams reinforced with FRP bars is also studied. A hole is provided at different locations along the span of the deep beam. The study revealed that the maximum reduction in the ultimate load carrying capacity of the deep beam is found to be 69.8% when the hole is provided on the inclined strut line located at the mid-depth of the beam.